Social Attention in Autism: Neural Sensitivity to Speech Over Background Noise Predicts Encoding of Social Information - Hernandez, Leanna M.; Green, Shulamite A.; Lawrence, Katherine E.; Inada, Marisa; Liu, Janelle; Bookheimer, Susan Y.; Dapretto, Mirella (Frontiers in Psychiatry, 2020)
Autism spectrum disorder (ASD) is a neurodevelopmental disorder characterized by lack of attention to social cues in the environment, including speech. Hypersensitivity to sensory stimuli, such as loud noises, is also extremely common in youth with ASD. While a link between sensory hypersensitivity and impaired social functioning has been hypothesized, very little is known about the neural mechanisms whereby exposure to distracting sensory stimuli may interfere with the ability to direct attention to socially-relevant information. Here, we used functional magnetic resonance imaging (fMRI) in youth with and without ASD (N=54, age range 8-18 years) to (1) examine brain responses during presentation of brief social interactions (i.e., two-people conversations) shrouded in ecologically-valid environmental noises, and (2) assess how brain activity during encoding might relate to later accuracy in identifying what was heard. During exposure to conversation-in-noise (vs. conversation or noise alone), both neurotypical youth and youth with ASD showed robust activation of canonical language networks. However, the extent to which youth with ASD activated temporal language regions, including voice-selective cortex (i.e., posterior superior temporal sulcus), predicted later discriminative accuracy in identifying what was heard. Further, relative to neurotypical youth, ASD youth showed significantly greater activity in left-hemisphere speech-processing cortex (i.e., angular gyrus) while listening to conversation-in-noise (vs. conversation or noise alone). Notably, in youth with ASD, increased activity in this region was associated with higher social motivation and better social cognition measures. This heightened activity in voice-selective/speech-processing regions may serve as a compensatory mechanism allowing youth with ASD to hone in on the conversations they heard in the context of non-social distracting stimuli. These findings further suggest that focusing on social and non-social stimuli simultaneously may be more challenging for youth with ASD requiring the recruitment of additional neural resources to encode socially-relevant information.